Avaliação da exposição e risco de câncer em trabalhadores da pavimentação: um estudo baseado nos níveis de partículas respiráveis presentes nos fumos de asfalto - Fontenele, Paulo Victor Gomes (2021)
Services in asphalt pavement are commonly employed in large urban centers. Recently, the International Agencyfor Research on Cancer (IARC) classified the external atmos-pheric particles as Group 1, i.e., proved to be carcinogenic to humans. In this way, the main objective of this study was to evaluate the levels of Respirable Particulate Mate-rial (RPM) in the asphalt fumes, as well as the health risk at the moment of the paving process, both in the plant and during the construction. The results of the study showed that the highest levels of RPM were found in the plant, being influenced mainly by the large production. The RPM obtained during the field application presented smaller concentrations and was influenced by the amount of asphalt material used, the tem-perature of the asphalt mixture during the application and the ventilation of the site. Daily exposure and risk of cancer were higher at the plant than in the field, and, at both places, these levels exceeded the main occupational health agencies recommenda-tions. The type of urban road influenced in the distribution of RPM levels and, conse-quently, in the exposure and risk of cancer to the pavement worker